Intestinal intraluminal injection of glutamine increases trolox total equivalent antioxidant capacity (TEAC) in hepatic ischemia-reperfusion - Salomão,Alberto Bicudo (2006)
PURPOSE: To evaluate the effects of intraluminal injection of glutamine on the serum trolox equivalent antioxidant capacity in an experimental model of ischemia-reperfusion of the liver observing the applicability of modifications on the original assay method. METHODS: Thirty Wistar rats underwent laparotomy to perform a 20 cm blind sac of small bowel and occlusion of the hepatic hilo for 30 minutes and reperfusion for 5 minutes. Into the gut sac it was injected glutamine (glutamine group, n=10) or distilled water (control group, n=10). Ten other animals (sham group) underwent laparotomy without artery occlusion. Blood samples were collected for trolox equivalent antioxidant capacity assays in different temperature conditions, reagent quantities and time for spectrophotometer readings. RESULTS: Total antioxidant capacity was significantly greater in glutamine group than in both control group (1,60[1,55-1,77] vs 1,44[1,27-1,53]) and sham group (1,60[1,55-1,77] vs 1,48[1,45-1,59]). CONCLUSION: Glutamine enhanced serum antioxidant capacity. The assay technique consistently reflected the changes in the antioxidant defenses in this experimental model.